Mobility for Academic Collaboration Post-COVID-19: Rebuilding Towards More Equitable Networks - Oanda, Ibrahim; Jon, Jae-Eun; Blanco, Gerardo (International Journal of African Higher Education, 2022)
In-person mobility has traditionally been taken for granted as an element of academic collaboration. The COVID-19 pandemic disrupted this status quo, introducing new challenges, especially across Africa, Asia and Latin America, where local economies and higher education systems have been disproportionately affected, exacerbating existing inequities. Low and unequal vaccination rates in these regions will likely continue to influence academic mobility. Given that international travel is set to remain complicated and expensive, African, Asian and Latin American academics’ preference for North America and Europe as destinations for mobility is likely to shift, with new academic mobility ecosystems emerging. Indeed, strong institutions and countries in these regions are becoming new hubs for intra-regional mobility and collaboration. The future of academic mobility and collaboration in Africa, Asia and Latin America is thus likely to include alternative destinations and virtual mobility, with the possibility of lower levels of international cooperation as the perceived value of mobility comes into question. These changes call for creative, long-term plans by institutions as well as governments. They present opportunities to promote mobility within regions, as well as South-South mobility in order to increase higher education’s social relevance.